Effect of temperature and water activity on growth and aflatoxin production by Aspergillus flavus and Aspergillus parasiticus on cured meat model systems. (December 2016) - Peromingo, Belén; Rodríguez, Alicia; Bernáldez, Victoria; Delgado, Josué; Rodríguez, Mar
Abstract: Dry-cured hams may be colonised by aflatoxin-producing Aspergillus flavus and Aspergillus parasiticus during the ripening process. The objective of this study was to evaluate the interaction between non-ionic water stress and temperatures may have on lag phases prior to growth, growth rates and aflatoxin production by two strains of each A. parasiticus and A. flavus on meat matrices over a period of 12 days. Results showed that A. flavus CBS 573.65 had shorter lag phases than A. parasiticus CECT 2688, however the growth rates were quite similar. For both species, no growth occurred at 10 °C and all aw tested and optimum growth happened at 25 °C and 0.95 aw. Similar aflatoxin B1 production profiles between both species were found, however A. flavus produced much higher concentration of such toxin than A. parasiticus . Both species produced aflatoxins when the temperature and the aw were ≥ 15 °C and ≥ 0.90. Highlights: Water activity and temperatures affect growth/aflatoxin production by Aspergillus . Maximum growth and aflatoxin production were observed at 25 °C and 0.95 aw . A. flavus produced much higher concentration of aflatoxin B1 than A. parasiticus . Temperature seems to affect aflatoxin production profile by A. parasiticus strains. Knowledge about Aspergillus ecophysiology on cured meats helps to control aflatoxin.